2024
DOI: 10.1002/cbf.3948
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide reverts multidrug resistance in KBChR 8‐5 cells through AKT signaling pathway

Deepa S. Lakra,
Pradhapsingh Bharathiraja,
T. Dhanalakshmi
et al.

Abstract: Multidrug resistance (MDR) is a major obstacle in cancer chemotherapy. P‐glycoprotein (P‐gp) one of the ATP‐binding cassette (ABC) transporters plays an important role in MDR. In this study, we examined the sensitizing property of andrographolide (Andro) to reverse MDR in the drug‐resistant KBChR 8‐5 cells. Andro exhibited increased cytotoxicity in a concentration‐dependent manner in the P‐gp overexpressing KBChR 8‐5 cells. Furthermore, Andro showed synergistic interactions with PTX and DOX in this drug‐resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(129 reference statements)
0
0
0
Order By: Relevance
“…45 Moreover, andrographolide in combination with paclitaxel and doxorubicin, mediates S-phase cell cycle arrest in drug-resistant KBChR-8-5 cells. 46 The gene expression analysis of major drug efflux ABC transporters such as ABCB1, ABCC1, ABCC2, ABCC3, ABCC5 and ABCG2 were studied using a PCR array in KBChR-8-5 cells. We found that KBChR-8-5 cells showed only ABCB1 overexpression.…”
Section: Additionally Morin Alone and Combination Treatment Downregul...mentioning
confidence: 99%
“…45 Moreover, andrographolide in combination with paclitaxel and doxorubicin, mediates S-phase cell cycle arrest in drug-resistant KBChR-8-5 cells. 46 The gene expression analysis of major drug efflux ABC transporters such as ABCB1, ABCC1, ABCC2, ABCC3, ABCC5 and ABCG2 were studied using a PCR array in KBChR-8-5 cells. We found that KBChR-8-5 cells showed only ABCB1 overexpression.…”
Section: Additionally Morin Alone and Combination Treatment Downregul...mentioning
confidence: 99%